Temporal trends of wild-type transthyretin amyloid cardiomyopathy in the transthyretin amyloidosis outcomes survey - Nativi Nicolau, Jose N.; Siu, Alfonso; Dispenzieri, Angela; Maurer, Mathew S.; Rapezzi, Claudio; Kristen, Arnt; Garcia-Pavia, Pablo; LoRusso, Samantha; Waddington-Cruz, Márcia; Lairez, Olivier; Witteles, Ronald; Chapman, Doug; et al. (JACC: CardioOncology, 2021)
Background - Transthyretin amyloid cardiomyopathy results from the accumulation of wild-type (ATTRwt) or variant (ATTRv) transthyretin amyloid fibrils in the myocardium. THAOS (Transthyretin Amyloidosis Outcomes Survey) is a global, longitudinal, observational survey of patients with ATTRv and ATTRwt amyloidosis and asymptomatic patients with transthyretin mutations. - Objectives - This study explored temporal trends in ATTRwt amyloidosis diagnoses using data from THAOS. - Methods - Using THAOS data from December 2007 to January 2020, the following comparisons were made according to year: ATTRwt amyloidosis diagnoses in the United States versus rest of the world, ATTRwt versus ATTRv amyloidosis with cardiac-associated mutations diagnoses, and ATTRwt amyloidosis diagnoses by tissue biopsy versus bone scintigraphy. - Results - There were 1,069 patients with ATTRwt amyloidosis and 525 with ATTRv amyloidosis with cardiac mutations enrolled in THAOS. The median time from symptom onset to ATTRwt amyloidosis diagnosis did not change over the past 5 years (>60 months from 2015-2019). ATTRwt amyloidosis diagnoses increased from 2 in 2005 to >100 per year from 2016, with a more pronounced increase in the United States compared with the rest of the world. Diagnoses of ATTRwt amyloidosis by tissue biopsy increased yearly and peaked in 2014 before declining, whereas diagnoses by bone scintigraphy increased markedly since 2011. ATTRv amyloidosis with cardiac mutation diagnoses increased from 3 in 2005 to 37 in 2011, then plateaued. The proportion of patients with ATTRwt amyloidosis diagnosed with New York Heart Association functional class III/IV heart failure decreased from 2012 (46.4%) to 2019 (16.0%). - Conclusions - In the past decade, ATTRwt amyloidosis diagnoses increased worldwide. Despite the growing utilization of bone scintigraphy, patients are diagnosed several years after symptom onset. (Transthyretin Amyloidosis Outcomes Survey [THAOS]; NCT00628745)